Making technology count for America's communities. - Celeste, Richard F. (Forum for Applied Research & Public Policy)
Downsizing, plant closings, job insecurity, worker anxiety: All have at times been blamed on innovations in technology and management. However, “The debate over jobs has been disconnected mostly from another, quieter one—the future mission and organization of the nation's enormously productive science-and-technology programs,” says Richard Celeste, a former governor of Ohio. Across the country, clusters of technology-oriented companies are turning their local communities into productive centers of growth. Celeste cites Boston's Route 128 and California's Silicon Valley as examples of successful technology clusters. “A new model for economic development...is helping communities as well as companies become more competitive. This model helps grow jobs while expanding grassroots support for innovation,” Celeste says. Reprinted by permission of the publisher.